Plant diversity and ethnobotanical importance of home gardens in Ghana's middle belt: a cross-sectional survey of the Sunyani municipality - Bismark Ofosu-Bamfo; Daniel Yawson; Kwame Baffour Asare; Vanessa Ohui Dadeboe; Isaac Kojo Buabeng; Justice Aggrey; Dery Aaron Dapillah; David Kojo Boateng; Emmanuel Offe; Thomas Abudu Alhassan (BMC, 2023)
Abstract Background Home gardens are a species-rich socioecological system with a diverse range of cultivated and naturally occurring plants with the potential to make contributions to address sustainable food, biodiversity and climate crisis. However, there is a dearth of information on the socio-demographic profile of home gardeners and the importance of home gardens to ethnobotany, food security and biodiversity. Therefore, the study aimed to assess the socio-demographic profile of home gardeners in the Sunyani municipality as a case in point for the middle belt of Ghana and to evaluate the diversity of plants in home gardens and their ethnobotanical importance. Methods A total of 12 suburbs were selected from three subzones in the Sunyani municipality. In each suburb, 25% of households were randomly selected and if they had a home garden, one adult in the house was interviewed. A list of all plants in the home garden and their uses was obtained from respondents. A Chi-square test was used to assess the distribution of home gardeners among various socio-demographic categories, and binomial logistic regression was employed to determine links between socio-demography and home garden attributes. The ethnobotany R package was used to evaluate the ethnobotanical importance of plants in home gardens. Results A total of 186 respondents were recruited for this study, 79 being females and 107 males. A total of 79 plant species were also identified belonging to 70 genera and 40 families. Trees were the most common plant life form in home gardens, followed by shrubs, herbs, vines, grasses and lianas. Ethnobotanical indices revealed the most important plants in home gardens to be staples, food supplements and medicinal plants. These were Musa paradisiaca, Caripa pabaya, Xanthosoma sagittifolium, Manihot utilisima and Mangifera indica, Moringa oleifera, Citrus sinensis, Capsicum frutescens, Taraxacum officinale, Solanum aethiopicum, Cocos nucifera, Solanum torvum, Persea americana, Dioscorea alata and Elaeis guineensis. Conclusion Plants used as staples, food supplements and medicinal purposes emerged as the most culturally relevant scoring high on all ethnobotanical indices. Home gardens present an opportunity to address food security and nutrition needs of households and communities.